Response time of elite female wrestlers - Gierczuk, D.; Luszczewska, O.; Tarsinska, A. (Polish Journal of Sport and Tourism, 2024)
Introduction. Response time is a crucial factor influencing performance effectiveness in wrestling. A short time of response enables athletes to engage in more effective technical and tactical actions. Despite numerous scientific studies on psychomotor abilities in combat sports, there is a lack of scientific reports on women`s wrestling, especially at the highest level of performance. The aim of this study was to determine the response time of female wrestlers with different levels of sports advancement and weight classes.